1996
DOI: 10.1111/j.1365-2230.1996.tb00059.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth of herpes simplex type 1 on skin explants of atopic eczema

Abstract: In a novel approach to looking at why some children with atopic eczema are susceptible to cutaneous herpes simplex virus (HSV) infections, this study evaluates the hypothesis that HSV replicates more easily on eczematous than normal skin. Growth of HSV on eczematous skin explants was compared with growth on explants from three control groups (psoriasis, Darier's disease and normal skin) over a 2-day period. Growth of HSV was significantly less on normal skin than in atopic eczema, psoriasis and Darier's diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…These alterations are possible candidate mechanisms for the serious consequences of herpes viruses and vaccinia virus in this skin disease. Goodyear et al (6) had previously observed increased quantities of HSV when cultured on skin explants obtained from patients with AD compared with skin from normal individuals. Thus, these experiments were performed in the absence of an adaptive immune response.…”
mentioning
confidence: 99%
“…These alterations are possible candidate mechanisms for the serious consequences of herpes viruses and vaccinia virus in this skin disease. Goodyear et al (6) had previously observed increased quantities of HSV when cultured on skin explants obtained from patients with AD compared with skin from normal individuals. Thus, these experiments were performed in the absence of an adaptive immune response.…”
mentioning
confidence: 99%
“…However, in a study to evaluate the growth of HSV1 on skin explants of patients with atopic eczema, HSV1 replicated quickly to a high titer in explants of both atopic dermatitis and psoriatic skin when compared with normal skin. 18 Currently, it is unknown whether the decrease in barrier function or the deficient host immune response allows increased susceptibility of patients with underlying dermatoses to HSV infection. One recent study evaluated the levels of plasmacytoid dendritic cells, which may play a role in host viral defense, in skin samples of patients with various inflammatory diseases and normal skin.…”
Section: Discussionmentioning
confidence: 99%
“…Wollenberg et al ,[8] reported reduced levels of plasmocytoid dendritic cells, which play a role in host viral defense, in skin samples of patients with atopic dermatitis when compared to psoriasis. Even though previously psoriatic skin was thought to be immune to KVE, a study by Goodyear et al ,[9] proved it otherwise. They found that HSV replicated quickly to a higher titre in explants of both atopic dermatitis and psoriatic skin when compared to normal skin.…”
Section: Discussionmentioning
confidence: 99%